2020
DOI: 10.21203/rs.3.rs-37255/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical, Perceptual, Socio-Relational and Affective Limitation of Five-Years-Old Children Born Preterm and Full-Term.

Abstract: Purpose: To compare the development of physical-motor, perceptual-motor and socio-relational and affective skills of five-years-old children born preterm and full term, completing the Checklist of Psychomotor Activities.Methods: A prospective simple ex-post facto study was conducted. The sample consisted of six hundred ninety-four (694) five-year-old children enrolled in the third year of early childhood education in the Province of Albacete-Spain. This study is based on medical histories - prior parental writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although the literature indicates, in general terms, that the practice of extracurricular physical activities favors FMS (Kokštejn et al, 2017), when the results obtained in different studies are analyzed in detail, it is found that not all FMS are benefited by this type of activity. Thus, for example, there are studies that show that in children as young as those that make up this sample, and also Spanish, only some motor components were benefited by these extracurricular activities (Gil-Madrona et al, 2021;Honrubia-Montesinos et al, 2021). Further research is required to clarify what characteristics should have motor extracurricular experiences to enhance the different FMS.…”
Section: Discussionmentioning
confidence: 94%
“…Although the literature indicates, in general terms, that the practice of extracurricular physical activities favors FMS (Kokštejn et al, 2017), when the results obtained in different studies are analyzed in detail, it is found that not all FMS are benefited by this type of activity. Thus, for example, there are studies that show that in children as young as those that make up this sample, and also Spanish, only some motor components were benefited by these extracurricular activities (Gil-Madrona et al, 2021;Honrubia-Montesinos et al, 2021). Further research is required to clarify what characteristics should have motor extracurricular experiences to enhance the different FMS.…”
Section: Discussionmentioning
confidence: 94%